XS, small houses big time - Baker, Lisa, 1982- (Salenstein : Braun, 2016)
Rising rents, the desire for a simpler life, the aim for sustainability, or the wish to posses a relocatable home: These are just a few reasons why the market for tiny houses has become increasingly popular in recent years. The Tiny House Movement lifestyle trend, which began in the Unites States, has spread throughout the entire world driven by the construction and financial crisis. Even though there are many regional variations, all residences of this type share a major feature on an area of up to 60 sqm (500 sqf) they provide all necessities of life. Nowadays, they are no longer designed by individual solo fighters but also by renowned architects who take on the simple yet challenging task and develop the enthralling room concepts and spatial solutions that are presented in this volume.
Includes indexes.
ARC
Karim International
Keywords: Small houses; Architecture, Domestic; Architecture